219 The Revised Edition of Korean Calendar for Allergenic Pollens - Oh, Jae-won (World Allergy Organization Journal, 2012)
BACKGROUND: The old version of pollen calendar was used until this year in South Korea. That calendar did not reflect current pollen distribution and concentrations that can be influenced by changes in weather and environment. A new pollen calendar of allergenic pollens was made based on the data on pollen concentrations obtained in 8 regions nationwide between 1997 and 2009 in South Korea. METHODS: The distribution of pollen grains was assessed every day at 8 areas (Seoul, Guri, Busan, Daegu, Jeonju, Kwangju, Kangneung, and Jeju) nationwide for 12 years between July 1, 1997 and June 30, 2009. Pollen were collected by using Burkard 7-day sampler (Burkard manufacturing Co Ltd, Hertfordshire, UK), and the collected pollens were sent every week to Hanyang Guri Hospital. Then pollens were strained with Calberla's fuchsin staining solution and were identified. The number of pollen grains per m(3) was calculated. RESULTS: Alder, birch and Japanese cedar started to appear in February. Japanese cedar showed a highest pollen concentration in Jeju. Pine became the highest pollen in May, and the pollen concentrations of oak and birch also became high. Common ragweed appeared in the middle of August and showed the highest pollen concentration in the middles of September. Japanese hop showed a high concentration between the middle of August and the end of September, and mugwort appeared in the middles of August and its concentration increased up until early September. Birch appeared earlier in Kangneung, and pine showed a higher pollen concentration than in the other areas. In Daegu, Oriental thuja, alder and juniper produced a large concentration of pollens. Pine produced a large concentration of pollens between the middle of April and the end of May. Weeds showed higher concentrations in September and mugwort appeared earlier than common ragweed. In Busan where is the southeast city, the time of flowering is relatively early, and alder and Oriental thuja appeared earliest among all areas. In Kwangju, Oriental thuja and hazelnut appeared in early February. In Jeju which is the end of southern island, Japanese cedar showed a higher pollen concentration than the other areas CONCLUSIONS: New information on pollen distributions and concentrations should be provided for the general publics or allergic patients through the website in order to prevent the occurrence of pollinosis.